Motivasi Belajar Siswa: Studi Eksperimental tentang Model Pembelajaran CTL pada Mata Pelajaran Aqidah Akhlak? - Intan Indah Maharany; Imam Syafe’i; Rudy Irawan (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This study aims to examine the effect of implementing the Contextual Teaching and Learning (CTL) model on students’ learning motivation in the Aqidah Akhlak subject. This research is motivated by the low level of students’ learning motivation, which is caused by the use of less varied instructional models and the lack of integration between learning materials and students’ real-life experiences, resulting in less meaningful learning. Therefore, instructional innovation is needed to enhance students’ learning motivation, namely through the implementation of the CTL model. This study employed a quantitative approach with a quasi-experimental design involving two classes: class X-B as the experimental group and class X-A as the control group at MA Al-Hikmah Bandar Lampung. Data were collected using a learning motivation questionnaire that had met validity and reliability requirements, with a Cronbach’s Alpha value of 0.650. Data analysis included normality testing, homogeneity testing, and an Independent Samples t-test. The results showed a significance value of 0.000 (< 0.05), indicating a significant difference in learning motivation between the experimental and control groups. These findings demonstrate that the implementation of the CTL learning model assisted by instructional videos is able to create more contextual, relevant, and meaningful learning, thereby increasing students’ learning motivation. The implications of this study suggest that the CTL model assisted by instructional videos can be used as an effective alternative instructional strategy in Aqidah Akhlak learning to enhance students’ learning motivation; therefore, this research is important to be conducted. Keywords : Aqidah Akhlak, CTL, Learning Model, Learning Motivation, Madrasah Aliyah